A non-proliferative role of pyrimidine metabolism in cancer - Siddiqui, Aarif; Ceppi, Paolo (Molecular Metabolism, 2020)
Background: Nucleotide metabolism is a critical pathway that generates purine and pyrimidine molecules for DNA replication, RNA synthesis, and cellular bioenergetics. Increased nucleotide metabolism supports uncontrolled growth of tumors and is a hallmark of cancer. Agents inhibiting synthesis and incorporation of nucleotides in DNA are widely used as chemotherapeutics to reduce tumor growth, cause DNA damage, and induce cell death. Thus, the research on nucleotide metabolism in cancer is primarily focused on its role in cell proliferation. However, in addition to proliferation, the role of purine molecules is established as ligands for purinergic signals. However, so far, the role of the pyrimidines has not been discussed beyond cell growth. Scope of the review: In this review we present the key evidence from recent pivotal studies supporting the notion of a non-proliferative role for pyrimidine metabolism (PyM) in cancer, with a special focus on its effect on differentiation in cancers from different origins. Major conclusion: In leukemic cells, the pyrimidine catabolism induces terminal differentiation toward monocytic lineage to check the aberrant cell proliferation, whereas in some solid tumors (e.g., triple negative breast cancer and hepatocellular carcinoma), catalytic degradation of pyrimidines maintains the mesenchymal-like state driven by epithelial-to-mesenchymal transition (EMT). This review further broadens this concept to understand the effect of PyM on metastasis and, ultimately, delivers a rationale to investigate the involvement of the pyrimidine molecules as oncometabolites. Overall, understanding the non-proliferative role of PyM in cancer will lead to improvement of the existing antimetabolites and to development of new therapeutic options.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Cancer; Chemoresistance; Epithelial-to-mesenchymal transition; Pyrimidine metabolism